Implementation of Pesantren Accounting in Financial Reporting - Isroin, Wahyuni; Marwazi; Adawiyah, Robi'atul (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study analyzes the implementation of pesantren accounting at Al-Jauharen Islamic Boarding School in the preparation of financial statements. The research focuses on the implementation process, the impact of training, and the challenges encountered in applying pesantren accounting at Al-Jauharen Islamic Boarding School. Method – This study employs a qualitative approach using the grounded theory method. Data were collected through observation, interviews, and documentation. The key informants included the leader, treasurer, former treasurer staff, current treasurer staff, auditor, secretariat, and CSR donature who provide insights into financial management. The data were also supported by financial reports and literature reviews. The analysis was conducted using NVivo 12, and the validity of the findings was tested through source triangulation. Findings – The implementation of accounting at Al-Jauharen Islamic Boarding School still faces challenges in financial recording, human resources, and technology. The current system is manual, relying on a General Cash Book and simple spreadsheets. Accounting training has raised awareness of transparency, but its implementation remains limited due to a lack of mentoring, competent human resources, and technological constraints. The main obstacles include limited funds for accounting system investment, the absence of specific accounting standards for pesantren, and a financial management culture based on trust without detailed record-keeping. Novelty – This study specifically identifies accounting constraints in pesantren, particularly technological limitations, human resources, and a trust-based financial management culture. Unlike previous studies, this research highlights the integration of sharia accounting and the urgency of financial record digitalization to enhance transparency. These findings serve as a foundation for developing a more systematic and adaptive pesantren accounting system. Keyword: Pesantren Accounting, Accountability, Financial Reports, Islamic Boarding School